Impact of Nonideal Nanoparticles on X‑ray Photoelectron Spectroscopic Quantitation: An Investigation Using Simulation and Modeling of Gold Nanoparticles - Sahoo, Smruti R; Ramacharyulu, P. V. R. K; Ke, Shyue-Chu (Analytical chemistry (Washington), 2018)
Quantitative X-ray photoelectron spectroscopic (XPS) analysis combined with spectral modeling of photoelectrons can be valuable while investigating the surface chemistry of nanoparticles (NPs) with different morphologies. Herein, with the use of NIST Simulation of Electron Spectra for Surface Analysis (SESSA), a comparative analysis of experimental and simulated photoelectron peak intensities in gold nanoparticles (AuNPs) of different morphologies is presented. Three sets of supported AuNPs with different morphologies were selected from a series of as synthesized Au-TiO2 catalyst samples. Using transmission electron microscopy (TEM) analyzed morphological information on the AuNPs as input model parameters in SESSA, XPS spectra were generated from the respective input NP morphologies. A degree of greater mismatch between SESSA simulated and experimental XPS spectra was observed while using the TEM obtained average diameter of the nanoparticles. The degree of mismatch lowered when the true nonspherical shape of the nanoparticles as obtained from TEM images was taken into account for the simulation. This demonstrates the impact of surface morphology on the XPS peak intensities which needs to be incorporated to obtain precise quantified information from the supported nanoparticles. This work demonstrates the applicability of SESSA in combination with experimental XPS and TEM measurements for precise quantification of XPS spectra from complex, nonideal shaped nanoparticles. This study can be extended to include a broad range of nanoparticles with ideal or nonideal geometries, thus providing a simple method to utilize quantitative XPS analysis to a wide range of nanomaterials.